Prognostic utility of the assessment of diastolic function in patients undergoing cardiac resynchronization therapy. (15th May 2021) - Galli, E.; Smiseth, O.A.; Aalen, J.M.; Larsen, C.K.; Sade, E.; Hubert, A.; Anilkumar, S.; Penicka, M.; Linde, Cecilia; Le Rolle, V.; Hernandez, A.; Leclercq, C.; et al.
Abstract: Conflicting data exist about the relationship between cardiac resynchronization therapy (CRT) and diastolic function. Aims of the study are to assess diastolic patterns in patients undergoing CRT according to the 2016 recommendations of the American Society of Echocardiography/European Association of Cardiovascular Imaging and to evaluate the prognostic value of diastolic dysfunction (DD) in CRT candidates. Methods and results: One-hundred ninety-three patients (age: 67 ± 11 years, QRS width: 167 ± 21 ms) were included in this multicentre prospective study. Mitral filling pattern, mitral tissue Doppler velocity, tricuspid regurgitation velocity, and indexed left atrial volume were used to classify DD from grade I to III. CRT-response, defined as a reduction of left ventricular (LV) end-systolic volume > 15% at 6-month follow-up (FU), occurred in 132 (68%) patients. The primary endpoint was a composite of heart transplantation, LV assisted device implantation, or all-cause death during FU and occurred in 29 (15%) patients. CRT was associated with a degradation of DD in non-responders. At multivariable analysis corrected for clinical variables, QRS duration, mitral regurgitation, CRT-response and LV dyssynchrony, grade I DD was associated with a better outcome (HR 0.37, 95% CI: 0.14–0.96). Non-responders with grade II-III DD had the worse prognosis (HR 4.36, 95%CI: 2.10–9.06). Conclusions: The evaluation of DD in CRT candidates allows the prognostic stratification of patients, independently from CRT-response. Highlights: Conflicting data exist about the relationship between cardiac resynchronization therapy (CRT) and diastolic function. CRT was associated with a degradation of diastolic dysfunction in non-responders. Grade I diastolic dysfunction was associated with a better outcome. Non-responders with grade II or grade III diastiloc dysfunction had the worse prognosis (HR 4.36, 95%CI: 2.10–9.06). So, the evaluation of diastolic dysfunction in CRT candidates is crucial for best stratification of patients according to their own risk of cardio-vascular event, independently from CRT-response.